THE IMPORTANCE OF SEMANTICS IN THE TEACIllNG OF LANGUAGE - Melaku, Asfaw; Lakew, WITekle (The Ethiopian Journal of Education, 2024)
Many linguists have adopted the name semantics to refer to the study of meaning of natural languages. Specialists in differentflelds have recognized the role semantics plays in language. At the same time other noted scholars have expressed different views about the place of semantics in the study of the grammar of a language. There are argumentsfor and against the importance of the meaning componnnt of the natural languages which were expressed by the structural, transformational generative, and semantic schools. The views presented in each of these cases seem to oppose one another even after some have revised their original ideas. These and the impotant role semantics plays in the communication process have very significant pedagogical implications to the practising language teacher.